Design agent based model to study the impact of social cohesion and victimization in the criminal behavior (2016)
In this research the construction of an agent-based model is proposed to study the impact of social cohesion and victimization in the process of decision making of a criminal. Modeling criminological aspects-established from theories of social disorder and routine activities in an architecture of artificial intelligence PECS (Physic, Emotion, Cognitive, Social), in order to articulate all dimensions involved in the construction of the decision. Social cohesion will be represented by social networks following the experiment done by Watts - Strogatz, and victimization as a cumulative result of previous victimizations. The results obtained in the simulation allowed to replicate social behavior main characteristics of a criminal Actor, because in them, the importance of the perception of social cohesion on the memory of victimization generated by past criminal events are highlighted. Elements that are consistent with the empirical evidence of the theoretical principles established in social disorder and routine actions.